ChemInform Abstract: Enantioselective Catalytic Reactions with N‐Acyliden Penta‐Atomic Aza‐Heterocycles. Heterocycles as Masked Bricks To Build Chiral Scaffolds. Issue 46 (November 2015) - Desimoni, Giovanni; Faita, Giuseppe; Quadrelli, Paolo
Abstract Review: 106 refs.